Faktor yang Berhubungan dengan Perilaku Pencegahan Diabetes Mellitus di Kelurahan Mlatiharjo Kecamatan Semarang Timur Kota Semarang - Dewi Insani Muflihah; Alfiana Ainun Nisa (Lembaga Pengembangan Kinerja Dosen, 2024)
Diabetes mellitus, which is a non-communicable disease, can be prevented by utilizing the power of prevention. Diabetes mellitus prevention behavior includes various aspects such as healthy eating patterns, sufficient physical activity, and regular health checks. It is important for the public to understand the risk factors for diabetes mellitus in order to improve prevention and early detection efforts in at-risk community groups. The aim of this research is to analyze the relationship between factors that influence diabetes mellitus prevention behavior in Mtahuarjo Village, East Semarang District, Semarang City. This research uses quantitative methods using observational analytics and a cross-sectional approach. The population in this research is the people of Mlagiarjo Village aged 20-79 years. The research sample was 197 respondents. This research was analyzed using univariate tests and bivariate tests. The results of the research showed that there was a relationship between knowledge, diet, physical activity, family history, family support, support from health workers, and access to health services (P-value = 0.024) with diabetes mellitus prevention behavior in Mtahuarjo Village, East Semarang District, Semarang City. . However, there is no relationship between attitudes and diabetes mellitus prevention behavior in Mtahuarjo Village, East Semarang District, Semarang City. It is important for health workers to provide education regarding diabetes mellitus prevention behavior to the public.